Counselling to include tailored use of combined oral contraception in clinical practice: an evaluation. Issue 1 (8th November 2017) - Akintomide, Hannat; Rank, Katherine Margaret; Brima, Nataliya; McGregor, Fiona; Stephenson, Judith
Abstract : Background: Combined oral contraception (COC, 'the pill') remains the most prescribed method of contraception in the UK. Although a variety of regimens for taking monophasic COC are held to be clinically safe, women are not routinely counselled about these choices and there is a lack of evidence on how to provide this information to women. Aim: To assess the usefulness and feasibility of including tailored use of monophasic COC within routine COC counselling in a sexual and reproductive health (SRH) service using a structured format. Method: Using a structured format, healthcare professionals (HCPs) counselled new and established COC users attending an SRH service about standard and tailored ways of taking the pill. Questionnaires were used to survey both the HCPs and patients immediately after the initial consultation, and then the patients again 8 weeks later. Results: Nearly all patients (98%, n=95) felt it was helpful to be informed of the different ways of using monophasic COC by the HCP, without giving too much information at one time (96%, n=108). The HCPs were confident of their COC counselling (99%, n=110) and did not think the consultations took significantly longer (88%, n=98). Conclusion: This study demonstrates that information on different pill taking regimens is useful and acceptable to patients, and can improve contraceptive pill user choice. It is also feasible for HCPs to perform COC counselling to include tailored pill use during routine consultations in a clinical setting.